THE DEVELOPMENT OF POLY SYNCHRONOUS-BASED E-LEARNING FOR EFL CLASSES AT THE ISLAMIC UNIVERSITY - Naajihah Mafruudloh; Fais Wahidatul Arifatin; Nur Mafissamawati Solikhah; Aries Fahriza; Dwi Wahyuningtyas (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
This study aims to develop e-learning and adapt the system to the needs of learning English. In addition, e-learning which can be used as asynchronous learning media can be integrated into learning media commonly used for synchronous learning also. So that all learning processes can be monitored and disciplined. In addition, the achievement of competence in learning English can be exceeded maximally. This research used the research and development (R&D) method with the ADDIE model. In this method, the researcher uses a descriptive quantitative approach. The assessment instruments used were test scores, interviews, observations, and interviews. The parties involved in this research were English lecturers, students, online learning media experts, and English learning material experts.